Effects of supplemental lysine, methionine, and threonine on weanling pigs fed a low-protein milo-soybean meal diet - Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three trials involving 331 weanling pigs (5 to 7 weeks old and weighing 20 to 33 pounds) were conducted to determine the effects of supplementing low-protein starter diets with crystalline amino aqids. In trials I and II, milo-soybean meal diets containing 12, 14, or 16% protein were supplemented so each contained the same quantity of lysine as an 18% protein, milo-soybean meal diet. Weight gain and feed efficiency of pigs fed the 16% protein lysine-supplemented diet was equivalent to that of pigs fed the 18% protein milo-soybean meal diet. Trial III evaluated 14, 16, 18, and 20% protein milo-soybean meal diets and the effects of supplementing the 14% protein diet with lysine, methionine, and threonine. In addition, the effects of supplemental lysine and methionine to the 16%proteindiet was also evaluated. Pigs performed similarly on diets containing 14% protein supplemented with lysine, methionine and threonine, 16% protein supplemented with lysine, and 18 or 20% protein milo-soybean meal diets. These studies indicate that a 16% protein milo-soybean meal diet supplemented with lysine is adequate for pigs weaned at 20 pounds.
Swine Industry Day 1973 is known as Swine Day, 1973
Keywords: Swine; Lysine; Methionine; Threonine; Protein; Milo-soybean meal